N-Arylphenothiazines as strong donors for photoredox catalysis – pushing the frontiers of nucleophilic addition of alcohols to alkenes - Speck, Fabienne; Rombach, David; Wagenknecht, Hans-Achim (Beilstein Journal of Organic Chemistry, 2019)
A new range of N-phenylphenothiazine derivatives was synthesized as potential photoredox catalysts to broaden the substrate scope for the nucleophilic addition of methanol to styrenes through photoredox catalysis. These N-phenylphenothiazines differ by their electron-donating and electron-withdrawing substituents at the phenyl group, covering both, σ and π-type groups, in order to modulate their absorbance and electrochemical characteristics. Among the synthesized compounds, alkylaminylated N-phenylphenothiazines were identified to be highly suitable for photoredox catalysis. The dialkylamino substituents of these N-phenylphenothiazines shift the estimated excited state reduction potential up to −3.0 V (vs SCE). These highly reducing properties allow the addition of methanol to α-methylstyrene as less-activated substrate for this type of reaction. Without the help of an additive, the reaction conditions were optimized to achieve a quantitative yield for the Markovnivkov-type addition product after 20 h of irradiation.
Keywords: addition; phenothiazine; photochemistry; photoredox catalysis; redox potential

(untitled) - Papadakis, R.; Ottosson, H. (Chem. Soc. Rev., 2015)

(untitled) - Rombach, D.; Wagenknecht, H.-A. (ChemCatChem, 2018)

(untitled) - Nguyen, T. M.; Manohar, N.; Nicewicz, D. A. (Angew. Chem., Int. Ed., 2014)

(untitled) - Shaw, M. H.; Twilton, J.; MacMillan, D. W. C. (J. Org. Chem., 2016)

(untitled) - Ghosh, I.; Ghosh, T.; Bardagi, J. I.; König, B. (Science, 2014)

(untitled) - Reckenthäler, M.; Griesbeck, A. G. (Adv. Synth. Catal., 2013)

(untitled) - Rueping, M.; Nikolaienko, P.; Lebedev, Y.; Adams, A. (Green Chem., 2017)

(untitled) - McTeague, T. A.; Jamison, T. F. (Angew. Chem., Int. Ed., 2016)

(untitled) - Lang, S. B.; Wiles, R. J.; Kelly, C. B.; Molander, G. A. (Angew. Chem., Int. Ed., 2017)

(untitled) - Lévesque, F.; Seeberger, P. H. (Angew. Chem., Int. Ed., 2012)

(untitled) - Amador, A. G.; Yoon, T. P. (Angew. Chem., Int. Ed., 2016)

(untitled) - Douglas, J. J.; Albright, H.; Sevrin, M. J.; Cole, K. P.; Stephenson, C. R. J. (Angew. Chem., Int. Ed., 2015)

(untitled) - Ohlow, M. J.; Moosmann, B. (Drug Discovery Today, 2011)

(untitled) - Discekici, E. H.; Treat, N. J.; Poelma, S. O.; Mattson, K. M.; Hudson, Z. M.; Luo, Y.; Hawker, C. J.; Read de Alaniz, J. (Chem. Commun., 2015)

(untitled) - Dadashi-Silab, S.; Pan, X.; Matyjaszewski, K. (Chem. – Eur. J., 2017)

(untitled) - Pan, X.; Fang, C.; Fantin, M.; Malhotra, N.; So, W. Y.; Peteanu, L. A.; Isse, A. A.; Gennaro, A.; Liu, P.; Matyjaszewski, K. (J. Am. Chem. Soc., 2016)

(untitled) - Christensen, J. A.; Phelan, B. T.; Chaudhuri, S.; Acharya, A.; Batista, V. S.; Wasielewski, M. R. (J. Am. Chem. Soc., 2018)

(untitled) - Kerzig, C.; Goez, M. (Chem. Sci., 2016)

(untitled) - Weiser, M.; Hermann, S.; Penner, A.; Wagenknecht, H.-A. (Beilstein J. Org. Chem., 2015)

(untitled) - Murphy, J. A.; Khan, T. A.; Zhou, S.-z.; Thomson, D. W.; Mahesh, M. (Angew. Chem., Int. Ed., 2005)

(untitled) - Ziegler, K.; Dislich, H. (Chem. Ber., 1957)

(untitled) - Ouardad, S.; Wirotius, A.-L.; Kostjuk, S.; Ganachaud, F.; Peruch, F. (RSC Adv., 2015)

(untitled) - Ruoff, R. S.; Kadish, K. M.; Boulas, P.; Chen, E. C. M. (J. Phys. Chem., 1995)

(untitled) - Senboku, H.; Komatsu, H.; Fujimura, Y.; Tokuda, M. (Synlett, 2001)

(untitled) - Mattay, J. (Tetrahedron, 1985)

(untitled) - Penner, A.; Bätzner, E.; Wagenknecht, H.-A. (Synlett, 2012)

(untitled) - Ong, S. P.; Chevrier, V. L.; Hautier, G.; Jain, A.; Moore, C.; Kim, S.; Ma, X.; Ceder, G. (Energy Environ. Sci., 2011)

(untitled) - Yasukouchi, K.; Taniguchi, I.; Yamaguchi, H.; Ayukawa, J.; Ohtsuka, K.; Tsuruta, Y. (J. Org. Chem., 1981)

(untitled) - Rehm, D.; Weller, A. (Ber. Bunsen-Ges., 1969)

(untitled) - Pavlishchuk, V. V.; Addison, A. W. (Inorg. Chim. Acta, 2000)

(untitled) - Hermann, S.; Wagenknecht, H.-A. (J. Pept. Sci., 2017)

(untitled) - Hermann, S.; Sack, D.; Wagenknecht, H.-A. (Eur. J. Org. Chem., 2018)